Exploring the communication gaps factor affecting the service delivery: a case study in Lembaga Hasil Dalam Negeri (LHDN) Sungai Petani Branch / Tengku Hilmi Tengku Abdul Kadir and Muhammad Haniff Muhammad Kamal - Tengku Abdul Kadir, Tengku Hilmi; Muhammad Kamal, Muhammad Haniff (2010)
This study examines the communication gap factors (integrated service marketing communication, managing customer expectations, propensity to overpromising and horizontal communication) effects toward service delivery in the organization of Lembaga Hasil Dalam Negeri (LHDN) Sungai Petani Branch. Other objectives are to find the most contributing factors of communication gap toward service delivery. The research uses the SERVQUAL Model, which is a concise multi-item scale with good reliability and reliability. It was designed by Zeithaml, Parasuraman, and Berry (1992) to be applicable across a broad spectrum or service culture. The hypotheses are tested using correlation and regression analysis. Simple linear correlation and regression is used to determine the linear relationship between the pairs of variables.